Community of practice EDU HUB: the training path - Benussi, Fulvio Oscar; Minozzi, Manuela (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
EDU HUB is a Community of Practice that was established in 2021 by secondary school teachers. The aim of the community is to compare peer-to-peer methodology on the practices implemented and co-design innovative teaching modules. The digitalisation of educational practices refers to the use of digital technologies to support teaching and learning activities. From a theoretical perspective, digitalisation offers several advantages. It enables more personalized and flexible learning experiences that can be tailored to the needs of individual students. Digital tools can also facilitate collaborative learning, allowing students to work together on projects and assignments regardless of their physical location.